Cinta sebagai Jiwa Kekudusan Gereja - Krishananta, Andreas Putra (Felicitas, 2021)
Holiness is the highest level in the Christian life. As the highest level, holiness becomes the goal of the Church's pilgrimage as a community of God's people. This was especially emphasized by the Second Vatican Council, namely that everyone is called to holiness (cf. LG, 39). The Church's journey to holiness is not an easy one. To come to holiness, people need love. Love is the soul that moves people to holiness. Therefore, love is called the soul of holiness. This paper intends to understand the idea of love as the holy soul of the Church and to draw a theological reflection on it.